Unmasking The Hidden Clues: Shedding Light On The Potential Of Novel Biomarkers In Endometrial Cancer, Comparing RT-Qpcr And Immunohistochemical Analysis In Clinical Specimens - Fatima, Sampana; Sabora, Ayman; Anwar, Iqra; Naeem, Seher; Abrar, Muhammad (Journal of Rawalpindi Medical College, 2025)
Objective: The objective of this study was to compare the diagnostic accuracy of RT-qPCR in endometrial cancer using novel biomarkers in clinical specimens, keeping immunohistochemical analysis as the gold standard. Methods: This cross-sectional validation study involved 210 endometrial biopsies, suspicious of endometrial carcinoma. RT-qPCR was performed, and relative gene expressions were calculated using the 2^-ΔΔCt method, with the endogenous control. Findings of the RT-qPCR were statistically analyzed keeping immunohistochemical analysis as the gold standard. Sensitivity, specificity, accuracy, negative predictive value (NPV) and positive predictive value (PPV) were calculated for the PCR technique. The clinical sensitivity of the test was determined by the Area under the curve (AUC)/Receiver Operating Curve (ROC). Results: RT-qPCR diagnosed 61 patients while histochemical analysis diagnosed 60 patients with endometrial carcinoma. RT-qPCR has shown a sensitivity of 96.67%, specificity of 98% and diagnostic accuracy of 97.62%. PPV and NPV of Rt-qPCR were 95.08% and 98.66%. Conclusions: RT-qPCR promises a highly sensitive and specific method for screening patients with endometrial carcinoma with expression of HE4, L1CAM, miR-200c, ARID1A, and PI3K. Keywords: Endometrial cancer, Immunohistochemical, biomarkers, radiotherapy.